A Numerical Research on Crack Process of Gypsum Containing Single Flaw with Different Angle and Length in Uniaxial Loading - Dai Bing; He Guicheng; Zhang Zhijun (Shock and Vibration)
To investigate the crack behaviour of rock or rock-like material in uniaxial loading, a series of numerical simulations were conducted on gypsum specimens containing a single flaw with different inclination angle (0°–90°) and length (10 mm–30 mm). Based on the numerical simulations results, the effect of flaw length on peak strength, the CI stress, and the CD stress were investigated with different inclination angles. The results show that the peak strength decreased initially and then increased with increasing of the flaw angle. Meanwhile, the peak strength decreased gradually when the length of the preexisting flaw increased. When the inclination angle was 30°, 45°, and 60°, the reduction degree of peak strength increased with increasing of the flaw length. The CI stress and CD stress not only depend on the inclination angle but also depend on flaw length. Four types of crack were observed in numerical simulations. The present research facilitates increased understanding of crack behaviour of rock under different conditions.